Os limites objetivos da coisa julgada - Carvalho, Abner Teixeira de (2020)
The res judicata, as an institute of law, proves to be fundamental to the stability of judicial decisions, giving the courts the security they seek in the legal relations they submit to. The study of this institute, however old, always returns to the stage of legal discussions, much for the improvement that ends up suffering with the new challenges to which it is submitted In Brazilian law the res judicata receives great attention from jurists, which leads the institute to gain increasingly sophisticated technical contours. From the institute's inception to the 2015 procedural codification, much has been seen to improve, starting with the recognition of the need for something that could give jurisdictional decision-making certainty to the scope of such decisions. The challenges of legal relations have led the judged thing to be thought through and rethought, being put to the test in everyday life, all in order to give legal certainty to the decisions of the judge state. The scope of what has been decided becomes important when the decision itself is brought into discussion, for the command of what has been decided stabilizes, but has real-world effects. It was up to the law to set the rules for decisions to become unchanged, as well as the people who will be affected and the object of the discussion itself, given that today also discusses the time when the decision will prevail, beyond the physical space. of its influence (territory). One of the limits that make up the res judicata is studied in this paper, namely, the objective limits of the res judicata, or in other words, what is decided, what is the object of the discussion brought to the judiciary that will receive the authority of legal certainty, which will become immutable (and hence undisputed). The way in which objective boundaries are handled by legal rules changed, when the 2015 Civil Procedure Code brought new thinking to the process, with an increasingly bureaucratic approach, greatly simplified it. The purpose of such changes is felt when there is a need to give more efficient answers to the problems brought to the judge state. The intention of this paper is to highlight this evolution, highlighting how the objective elements of the judged thing are treated in procedural coding, before and now. The most recent doctrinal stance, as well as, in conclusion, the idea that the objective limits of the res judicata can, however academically, extend further and become more efficient in response to the jurisdictional